The Influence of Celebrity Endorser and Product Quality on Purchasing Decisions for Scarlett Products (Case Study of Scarlett Product Customers in Cimahi City) - Moh Aep Nurjamad; Eriyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The goal of this study was to ascertain how much influence celebrity endorsers and product quality have on purchasing decisions for Scarlett products. The research methods used are descriptive methods and associative methods. Scarlett product customers in Cimahi City are the unit of analysis on this study. Based on the results of the sample calculation using the lemeshow formula because the population is not known with certainty, there were 96 respondents in the study's samples. Multiple linear regression analysis is the technique utilized for analysis, in addition, t-test and F-test are also carried out. The findings of the research, the dependent variable (purchasing decision) is influenced by the independent factors (celebrity endorser and product quality) by 72.5%. The influence of celebrity endorser factors on purchasing decisions is 5.6%. While the influence of product quality is 66.9%. The implication of this research is that Scarlett products can review the criteria for using celebrity endorsers by having a good image and continuing to improve product quality for the better so that it can increase customer purchasing decisions